Undergraduate nursing students caring for cancer patients: hermeneutic phenomenological insights of their experiences - Charalambous Andreas; Kaite Charis (BMC, 2013)
Abstract Background The care of patients suffering from cancer and especially those facing the death trajectory appears to be complex and demanding not only for student nurses but for professional nurses as well. The educational models often used in nursing require students to face challenging care scenarios, sometimes with minimal or no supervision and guidance. These "worst case scenarios" can be traumatic experiences that can leave the student hopeless and disappointed of themselves and in many cases can "scar" their subsequent professional career. The literature demonstrates that this can be the result of the students' ill-preparation to care for cancer patients and deal with death and dying. The purpose of this study was to interpret the students' experiences of coming face-to-face with cancer care during their clinical placements. Methods This is a hermeneutic phenomenological study influenced by the ideas of the French Philosopher Paul Ricoeur. Based on this philosophical enquiry the interpretation process included three stages: 1) naïve reading, 2) structural analysis and 3) comprehensive understanding. Data were collected through reflective/narrative diaries from the 4th grade undergraduate (pre-registration) nursing students practicing at oncology, hematology, pediatric oncology departments and hospices. Diaries of twelve students met the inclusion criteria and were included in the interpretation process. The study took place during January and May 2011. Results The interpretation yielded the following themes: a) Being part of the center's life, b) Being sympathetic, c) Being confronted by others, d) Being self-reflective, e) Being trapped in the system, f) Being caring towards the family and g) Being better in clinical practice. Conclusions The students emphasized the need for appropriate preparation both at a theoretical and at a clinical level, as to better confront situations involving death and dying as well as learning techniques for crisis management. The students perceived the importance of adopting a policy that is both patient and family-centered in order to provide better care.